A study investigating teachers’ use of, and views on, tablets in the teaching of mathematics - Petrovai, K (2018)
Digital technologies are often positioned as having great potential for teaching and learning. However, adoption, particularly in mathematics education, has been slow. More recently there has been increasing focus on the role teachers play in the way digital technologies are used in the classroom. When considering the available research in this area, we observe that there is still little work that is integrated in the busy and unpredictable school environment in which teachers use digital technologies. With the added complexity that many of the digital technologies adopted by schools, such as tablets, incorporate a wide spectrum of programs it is crucial to understand how teachers use and view digital technologies. In partnership with a comprehensive British school that has implemented a one-tablet-per-student programme, this study investigated the way four Year 8 mathematics teachers’ use of, and views on, tablets in their teaching developed over time, and the factors impacting them. The study was situated in a natural school setting, with the added dimension that teachers met as a group to discuss their use of, and views on, tablets while exchanging knowledge about using tablets in their teaching. The data collected included audio recordings of the group meetings, individual teacher interviews at the start of the study, classroom observations, and short interviews with teachers directly following each observed lesson. Building on research that has looked at the ways teachers can, or do, use digital technologies in the teaching of mathematics, this study developed a framework that incorporated a wide spectrum of ways digital technologies can be used in mathematics classrooms. The framework, named the Teacher Adoption of Digital Technologies framework, articulates the increasing complexity with which technology can be used in the teaching and learning of mathematical tasks and incorporates characteristics of tasks that teachers use in the classroom such as their instrumental evolution, efficiency, engagement, and focus. In addition, the framework captures the teachers’ views of using technology and the knowledge exchanged during group meetings. The key findings of this study highlight that: (1) teachers used tablets to support mathematics teaching in tasks that had little variation in their instrumental evolution but were designed to promote efficiency, engagement, and focus; (2) teachers viewed tablets as useful but had mixed self-efficacy in their ability to use them in new ways; (3) factors that impacted teachers’ decisions to use the tablets were mainly classroom management, finding useful resources, and having appropriate support from school leadership; and (4) teachers found the group meetings useful to exchange their knowledge and experience of using technology and to develop their use and views of tablets. It is hoped that the outcomes of this study will guide future implementations of technologies in schools and teacher development, contributing to the way teachers can use and innovate with tablets in teaching mathematics.